2004
DOI: 10.1080/0141192042000195263
|View full text |Cite
|
Sign up to set email alerts
|

Values education: the development and classroom use of an educational programme1

Abstract: The article is concerned with values education in schools in the light of the requirement for schools to provide for the spiritual, moral, cultural and social development of children and in the light of wider discussions regarding 'spirituality' in (post)modern society. The authors focus on Living Values, a programme developed as a way of introducing values-based education to schools as well as to the wider community. They examine both the contents of the programme and the way it reaches schools and is utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
16
0
3
Order By: Relevance
“…In the implementation, it was found that character education is education of value. On the other hand, education of value is an education to form a character (Arweck & Nesbitt, 2004;Thompson, 2002;Katilmis et al, 2011;Benninga, Berkowitz, Kuehn, & Smith, 2013;Susiastik, 2018), in which it is in accordance with the dimension of moral process offered by Lickona (2004). Such a thing happens since basically, a value is a core component of a human's character (Al-Ani, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the implementation, it was found that character education is education of value. On the other hand, education of value is an education to form a character (Arweck & Nesbitt, 2004;Thompson, 2002;Katilmis et al, 2011;Benninga, Berkowitz, Kuehn, & Smith, 2013;Susiastik, 2018), in which it is in accordance with the dimension of moral process offered by Lickona (2004). Such a thing happens since basically, a value is a core component of a human's character (Al-Ani, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The two values programmes under consideration need to be set against the wider educational context, which can be seen as three overlapping spheres (also Arweck & Nesbitt, 2004b). The first comprises a set of values-related educational initiatives and approaches, which originate and are located outside the common school system, but seek to influence it -for example, initiatives like Human Scale Education 15 or Antidote, 16 schools based on a particular Weltanschauung, and other 'alternatives to education'.…”
Section: The Educational Contextmentioning
confidence: 99%
“…They add that according to the designers of this program, these values are universally acceptable and they should be encouraged in people so as to make the world a better place to live. Halstead defines values as "principles, fundamental convictions, ideals, standards or life stances which act as general guides to behavior or as reference points in decision-making or the evaluation of beliefs or action" (1996 quoted in Arweck & Nesbitt 2004). In Arweck and Nesbitt's opinion, the values are a response to "the call for values" in a world in which children are influenced by social difficulties, violence, and a lack of respect.…”
Section: Valuesmentioning
confidence: 99%
“…These changes are all positive as they indicate that universities have grasped the importance of values and they are willing to educate their students in this respect as well by acting towards the goal of equipping their students with ethical values and moral responsibilities. Arweck and Nesbitt (2004) state that "values-based education can be seen as a kind of tool-kit for children and young people as well as adults in thinking about the values in their lives, applying them in dealing with relationships and social situations, and shaping attitudes towards others, property, and social structures". According to Ashton and Watson (1998), values education must encourage an approach that is really educational, rather than dependent on authority structures.…”
Section: Valuesmentioning
confidence: 99%
See 1 more Smart Citation